Capital Structure, Sales Growth, and CSR as Drivers of Financial Performance: Evidence from Indonesia's Food and Beverage Sector with Firm Size as a Moderator - Yayu Kusdiana; Nanda Suryadi; Arie Yusnelly; Jenita Jenita; Mazzlida Mat Deli; Siti Intan Nurdiana Wong Abdullah (International Journal of Information System and Innovation Management (IJISIM), 2026)
This study was conducted to analyze the effect of capital structure, sales growth, and corporate social responsibility (CSR) on financial performance, with firm size functioning as a moderating variable in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research applied a purposive sampling method and obtained 60 samples from a total population of 98 companies. The data were analyzed using panel data regression with EViews 12 software. The results demonstrate that capital structure positively affects financial performance, while sales growth and CSR negatively affect financial performance. Furthermore, firm size weakens the influence of capital structure but strengthens the influences of sales growth and CSR on financial performance. The coefficient of determination (R²) value of 60.56% signifies that the research variables collectively explain 60.56% of financial performance, whereas the remaining 39.44% is explained by other variables outside this study.